ESSENCE, OBJECTIVES AND LEGAL REGULATION OF LABOR AND WAGE ACCOUNTING - Khudoynazar Ergashev; Guljakhon Klicheva (Journals Park Publishing, 2023)
Accounting for labor and wages is a central issue in the entire accounting system of an enterprise. Any process of economic activity is associated with the costs of not only means (objects) of labor, but also with the costs of living labor [2]. Each employee of an enterprise who works for hire receives a salary from the employer for the work done - a certain amount of money that compensates for his labor costs and provides him with a certain level of satisfaction of personal needs, as well as the needs of his family members, which can take two forms - monetary (the most acceptable) and material [1].
Keywords: forms, systems, amounts, remuneration, material incentives, results, bonuses, additional payments, allowances and social benefits.